HUBUNGAN PENGETAHUAN IBU TENTANG RESPONSIVE FEEDING DENGAN STATUS GIZI BALITA USIA 12-36 BULAN DI PUJOTIRTO KABUPATEN KEBUMEN - Meivita Purnamasari; Devita Febriani; Dian Ramawati (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2023)
Multiple nutritional problems include undernutrition and over nutrition at the age of five. Proper feeding by mother through responsive feeding can support the fulfillment of nutrition and give an impact on the nutritional status of children. The purpose of this research was to determine the relationship between mother's knowledge about responsive feeding and the nutritional status of toddlers aged 12-36 months. The research was a quantitative study using a cross-sectional research design. The research sample is 68 respondents. The instrument used a questionnaire. Methods of data analysis used univariate analysis on education, occupation, age, level of mother's knowledge about responsive feeding, and developmental status of toddlers as well as bivariate analysis to analyze the relationship between mother's knowledge about responsive feeding and nutritional status of toddlers aged 12-36 months. The results of the research that has been done show that mother's knowledge is in the good category of 52.9%, sufficient 23.8% and less 13.2%. An overview of the nutritional status of toddlers in the good weight category is 70.6%, the risk of being over weight is 19.1%, and the underweight is 10.3%. The results of the Somers’ d analysis showed that there was a relationship between mother's knowledge about responsive feeding and the nutritional status of toddlers aged 12-36 months which was indicated by a p value <0.05. Research recommends the need for responsive feeding education for toddler mothers.